Impact of the Covid-19 pandemic on radiography & radiotherapy practice in Malaysia - Mohd Izuan Ibrahim,; Rahmahwaty Akib,; Mohd Farihan Jaffar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aimed to evaluate the COVID-19 pandemic impact on radiography and radiotherapy practice in Malaysia. An online cross-sectional survey was conducted from July to October 2020 among radiographers. The questionnaire was adapted from the previous study. A total of 214 (female, n=148 and male, n=66) responses were received comprising 79.9% diagnostic and 20.1% therapeutic radiographers across Malaysia. The data were analyzed using IBM SPSS Version 25.0. The results show that 71% agree that the radiographers are part of the major frontline and 50.9% agree diagnostic radiographer’s workload increases. Besides, 77.1% and 71.9% of them are very aware of the COVID-19 virus transmission and infection control principle, respectively. Furthermore, 59.8% stated that adequate personal protective equipment (PPE) was provided by the department while 57% receive adequate training in handling patients during the pandemic. There were 66.5% and 28.6% of diagnostic radiographers and therapeutics radiographers who receive specific training in facing COVID-19 patients. During the pandemic, only 29% feel frequently stressed about work and 62.1% sometimes. The significant association χ2 (p=0.0002) exists between radiographers and the perception of stress. Most of the radiographers rate their level of stress between 5 to 8 on a scale of 1 (no stress) to 10 (highly stress). In conclusion, increasing workload during the pandemic increase the level of stress among radiographers. However, adequate PPE, a good work rotation schedule, and training will help them facing the pandemic.